Metal-organic framework-based nanomaterials for bone tissue engineering and wound healing. (March 2022) - Asadniaye Fardjahromi, M.; Nazari, H.; Ahmadi Tafti, S.M.; Razmjou, A.; Mukhopadhyay, S.; Warkiani, M.E.
Abstract: Over the past decade, tremendous growth has been witnessed in the synthesis of scaffolds fabricated by natural or synthetic, composite, or hybrid biomaterials to enhance wound healing, repair of bone fractures, and pathological loss of bones. However, the current limitations of using these scaffolds in tissue engineering are impaired cellular proliferation, poor differentiation, low mechanical stability, and bioactivity. Recent advances in the fabrication of nanoscale metal-organic framework (nano-MOF) scaffolds have provided golden opportunities to enhance the properties of scaffolds in bone and wound tissue engineering. In the past few years, studies have shown that incorporating nano-MOFs into scaffolds can be highly favorable in the regeneration of imperfect tissues owing to their unique properties such as high internal surface areas, high porosity, good mechanical stability, biocompatibility, and tunability. Moreover, the nanoscale structural and topological properties of nano-MOFs enhance the physicochemical properties of scaffolds, enrich them with drug-loading and ion-releasing capacity, and regulate stem cell attachment, proliferation, and differentiation after transplantation. This review initially introduces the various nano-MOFs incorporated into scaffolds for tissue engineering. Recent applications of nanoMOFs for bone and wound healing are comprehensively discussed. The unique properties of nano-MOFs for improving osteoconductivity, osteoinductivity, and wound healing, such as high antibacterial activity, high drug loading capacity (i.e., bioactive molecules and growth factors), and controlled drug release, are discussed. Finally, challenges, clinical barriers, and considerations for implementing these nanomaterials in different scaffolds, tissue-like structures, implants, fillers, and dressers in the orthopedic and wound clinics are comprised. Graphical abstract: Image 1 The applications of nano-MOFs for bone tissue engineering and wound healing. The schematic shows different components, frameworks, stimuli-responsive systems, and available fabrication methods for synthesizing nano-MOFs. The nano-MOFs can be incorporated into scaffolds through different methods, including three-dimensional printing, cathode electrode deposition, and selective laser sintering for tissue engineering applications. The nano-MOF-based scaffolds enhance the regeneration, angiogenesis, and antibacterial properties of scaffolds by releasing metallic ions, vitamins, and nitric oxide gas in the wound site. In addition, in terms of bone regeneration, nano-MOFs accelerate the healing process by delivering signaling molecules, growth factors, drugs, antibacterial agents, and ions to the fracture site. Highlights: Nano-MOFs can improve scaffolds' biological, physical, and mechanical properties for bone and wound healing. Nano-MOFs can be fabricated in different shapes and sizes, with stimuli responsivity for different clinical approaches. Nano-MOF improve osteoconductivity, osteoinductivity, and mechanical properties of bone scaffolds for bone healing. Nano-MOFs can be used as antibacterial agents and nanocarriers to deliver antioxidants and biomolecules. Further investigation needs to overcome the challenges and clinical barriers of nano-MOF scaffolds.